Farmers’ personality traits and credit exclusion: Evidence from rural China - Tian, Yaqun; Fan, Yachen; He, Guangwen (Frontiers in Psychology, 2022)
Unlike existing research from the perspective of financiers or farmers’ financial literacy, this paper discusses the impact of personality traits on Chinese farmers’ credit exclusion. Based on data from the 2018 and 2019 China Rural Inclusive Finance Survey by China Agricultural University, this paper uses the “Big Five” personality classification to measure personality traits and examine the impact of farmers’ personality traits on credit exclusion. The results show that personality traits significantly affect the degree of credit exclusion; conscientiousness and extroversion can significantly reduce the possibility of credit exclusion, while agreeableness can significantly increase the degree of credit exclusion. In addition, the Blinder-Oaxaca decomposition method was used to analyze personality traits’ contributions to each dimension of credit exclusion, finding that personality traits mainly affected farmers’ self-exclusion. Therefore, to develop inclusive finance in China, training and improving farmers’ positive personality traits must be fostered.